Distinctive Evasion Mechanisms to Allow Persistence of Borrelia burgdorferi in Different Human Cell Lines - Karvonen, Kati; Nykky, Jonna; Marjomäki, Varpu; Gilbert, Leona (Frontiers in Microbiology, 2021)
Lyme borreliosis is a multisystemic disease caused by the pleomorphic bacteria of the Borrelia burgdorferi sensu lato complex. The exact mechanisms for the infection to progress into a prolonged sequelae of the disease are currently unknown, although immune evasion and persistence of the bacteria in the host are thought to be major contributors. The current study investigated B. burgdorferi infection processes in two human cell lines, both non-immune and non-phagocytic, to further understand the mechanisms of infection of this bacterium. By utilizing light, confocal, helium ion and transmission electron microscopy, borrelial infection of chondrosarcoma (SW1353) and dermal fibroblast (BJ) cells were examined from an early 30 min time point to a late 9 d post-infection. Host cell invasion, viability of both the host and B. burgdorferi, as well as, colocalization with lysosomes and the presence of different borrelial pleomorphic forms were analyzed. The results demonstrated differences of infection between the cell lines starting from early entry as B. burgdorferi invaded BJ cells in coiled forms with less pronounced host cell extensions, whereas in SW1353 cells, micropodial interactions with spirochetes were always seen. Moreover, infection of BJ cells increased in a dose dependent manner throughout the examined 9 days, while the percentage of infection, although dose dependent, decreased in SW1353 cells after reaching a peak at 48 h. Furthermore, blebs, round body and damaged B. burgdorferi forms were mostly observed from the infected SW1353 cells, while spirochetes dominated in BJ cells. Both infected host cell lines grew and remained viable after 9 d post-infection. Although damaged forms were noticed in both cell lines, colocalization with lysosomes was low in both cell lines, especially in BJ cells. The invasion of non-phagocytic cells and the lack of cytopathic effects onto the host cells by B. burgdorferi indicated one mechanism of immune evasion for the bacteria. The differences in attachment, pleomorphic form expressions and lack of lysosomal involvement between the infected host cells likely explain the bacterium’s ability to adapt to different environments, as well as, a strategy for persistence inside a host.